The effects of stocking rate, residual sward height, and forage supplementation on forage production, feeding strategies, and productivity of milking dairy cows - Ortega, Gastón; Berberian, Natalia; Chilibroste, Pablo (Frontiers in Animal Science, 2024)
The intensification process in Uruguayan dairies over the last 30 years has involved increases in stocking rate (SR) and individual milk production. This research aimed to compare biophysical indicators along with the associated feeding strategies for Holstein-Jersey crossbred dairy cow systems. The comparison was conducted in farmlets representing a typical Uruguayan pasture-based dairy system on a grazing area (i.e., area where cows have direct access to grazing). The study spanned from 2017 to 2019, combining 1.5 or 2.0 milking cows per hectare (SR), with two different residual sward heights (RH) -LR (6-7 cm maintained all year round) and HR (a grazing management with a higher residual, averaging 9-10 cm). These combinations resulted in four treatments: 1.5LR, 1.5HR, 2.0LR, and 2.0HR. Ninety-six cows were randomly allocated to each treatment based on parity, body weight (BW), and body condition score (BCS) for the years 2017, 2018, and 2019. Response variables per hectare were analysed using a linear mixed model that include SR, RH, their interaction effect, year and paddock as a repeated measurement. Forage production did not differ between treatments, and forage directly harvested by cows was affected by SR, with SR 2.0 higher than SR 1.5. Milk productivity was impacted by SR (SR 2.0 produced 4318 L/ha and 347 kg milk solids/ha per year more than SR 1.5) an interaction effect was detected between SR and RH on milk and milk solids productivity: 2.0 HR treatment was higher than 2.0 LR but treatments on SR 1.5 were not different between them. The consumption of concentrate, forage and conserved forage per ha was influenced by SR.Besides, cows on 2.0HR consumed more concentrate per ha than cows on SR 2.0LR. Individual milk production was not influenced by SR or RH. Treatment 2.0HR had higher DMI per cow than 1.5 LR and 1.5 HR but were not different from 2.0LR.Concentrate DMI per cow was not different between treatments while conserved forage DMI per cow was higher for SR 2.0 than SR 1.5. This research highlights different approaches to enhance the competitiveness of Uruguayan grazing systems through improvements in forage harvest.